Distinctness, phylogenetic relations and biogeography of intertidal mussels (Brachidontes, Mytilidae) from the south-western Atlantic - Trovant, Berenice (2013)
Rocky shore intertidal communities along the cold- and warm-temperate coasts of the south-western Atlantic are dominated by small mussels of the genus Brachidontes s.l. (Mytilidae), yet the status of species occurring in the region remains unresolved. Taxonomic studies have been based on shell morphology, but high phenotypic variability has led to much confusion. Based on mitochondrial and nuclear genes (COI, 28S rDNA and ITS1) from nine localities in Uruguay and Argentina we confirmed the occurrence of three species in the south-western Atlantic: Brachidontes darwinianus and B. rodriguezii in the warmtemperate and B. purpuratus in the cold-temperate sector. The latter two species coexist in the same beds along the transition zone (41?438S). The phylogeny based on mitochondrial and nuclear genes, indicate an early divergence of B. purpuratus. At the intra-specific level, low genetic differentiation and absence of fossil record for B. purpuratus from the earlier Quaternary marine terraces of Patagonia likely result from a relatively recent (post-LGM) colonization originated from populations in the southeastern Pacific. In the case of B. rodriguezii, by contrast, genetic intraspecific differentiation, a fossil record of phenotypically-related forms going back to the Late Miocene, and phylogenetic position in the COI-based phylogeny, prompts the hypothesis that this species is derived from a local stock with a long history of occurrence in the warm-temperate region of the south-western Atlantic. While intertidal mussel beds from the south-western Atlantic are ecologically similar in appearance, their assembly involves components clearly differentiated in terms of historical biogeography and phylogeny.